Staphylococcus Aureus Biofilms Induce Apoptosis and Expression of Interferon-γ, Interleukin-10, and Interleukin-17A on Human Sinonasal Explants. Issue 1 (January 2015) - Cantero, Daniel; Cooksley, Clare; Bassiouni, Ahmed; Tran, Hai Bac; Roscioli, Eugene; Wormald, Peter-John; Vreugde, Sarah
Background: Staphylococcus aureus is one of the most common bacteria associated with chronic rhinosinusitis (CRS). Although S. aureus biofilms have been correlated with disease severity in CRS, little is known about the initial immune response that biofilms induce in the sinonasal mucosa. Objective: The aim of this study was to evaluate the innate immune response (in terms of cytokines) of nondiseased human sinonasal tissue to S. aureus biofilms. Methods: Full-thickness sinonasal explant cultures (n = 7 donors) were challenged with established S. aureus biofilms for 24 hours. The expression profiles of 17 cytokines were measured using multiplex analysis, real-time quantitative reverse transcription polymerase chain reaction, and immunohistochemistry. Differences in expression were evaluated using Student's t-test. Results: Interleukin (IL)-1β, IL-10, TNF, IL-17A, and interferon (IFN)-γ were up-regulated at the RNA and protein levels in biofilm-treated tissues compared with controls. Elevation of caspase-3 in biofilm-treated samples indicates S. aureus biofilms induce apoptosis on the sinonasal mucosa. Conclusion: S. aureus biofilms induced apoptosis and a predominant proinflammatory immune response on normal sinonasal mucosal explants. This immune response appeared to be triggered by intrinsic bacterial elements but also by components of the biofilm matrix. Live biofilms were present on the mucosa at the end of the challenge, suggesting an inability of the induced immune response to eliminate the S. aureus biofilms.